Insulation measurement and supervision in live AC and DC unearthed systems - Olszowiec, Piotr (Lecture Notes in Electrical Engineering, 2014)
Low voltage unearthed (IT) AC and DC systems are commonly applied for supply of power and control circuits in industry, transportation, medical objects etc. The main reasons for their use are high reliability and numerous advantages offered by isolating them against ground. Insulation level is a decisive factor for networks operational reliability and safety. Insufficient insulation-to-ground resistance can cause various disturbances. Though ground faults in IT systems do not make networks operation impossible, they may cause severe problems with their safe functioning. In this book the most important issues concerning normal operation and ground fault phenomena are described in concise form. Numerous methods of insulation resistance and capacitance measurement in live circuits are presented. Important other procedures of  these parameters determination based on measurement and calculation are explained and reviews of selected insulation resistance measurement devices as well as earth fault locating systems are included. This book is addressed to electrical engineers, technicians and students and may also serve as an academic handbook. The extended second edition includes several innovative methods of insulation parameters determination as well as more detailed explanations of procedures and issues. Furthermore new important problems e.g. indirect methods of insulation resistance determination and insulation resistance monitoring in networks with frequency converters are addressed as well as examples of practical applications.